Safety in passenger ships: The influence of environmental design characteristics on people's perception of safety. (March 2017) - Ahola, Markus; Mugge, Ruth
Abstract: Although objective safety is a widely studied topic in ergonomics, subjective safety has received far less research attention. Nevertheless, most of human decision-making and behavior depends on how we perceive our environment. This study investigates the effects of various environmental design characteristics on people's safety perception in a passenger ship context. Five different environmental design characteristics were manipulated to increase the openness of the space or to create more clear navigation, resulting in 20 different cabin corridors for a passenger ship. Ninety-seven respondents were asked to rate these corridors on the perceived safety in an experiment. The results showed that people feel more safe when the corridors have a curved ceiling, when the walls do not have a split-level design, and when there is a view to the outside. Designers can use these insights when designing future environments. Highlights: People's safety perception is influenced by environmental design characteristics. Openness and giving guidance are important for improving people's safety perception. Curved ceiling design positively affects people's safety perception. Complexity in the environmental design negatively affects people's safety perception. Having a view to the outside positively affects people's safety perception.